Essential do's and taboos : The complete guide to international business and leisure travel - Axtell, Roger E. (New Jersey John Wiley & Sons, Inc., 2007)
The content of this book includes: Information on customs, protocol, etiquette, hand gestures, and body language Fresh advice regarding Internet business and communication options Country-specific chapters on eleven popular locations Guidance on hosting international visitors Important tips on using English around the world Special do's and taboos for women traveling abroad
Includes index
Keywords: Cơ bản